Hepatoprotective effect of ethanolic extract of Curcuma longa on thioacetamide induced liver cirrhosis in rats - Salama, S.M.; Abdulla, M.A.; AlRashdi, A.S.; Ismail, S.; Alkiyumi, S.S. (BioMed Central, 2013)
Background Hepatology research has focused on developing traditional therapies as pharmacological medicines to treat liver cirrhosis. Thus, this study evaluated mechanisms of the hepatoprotective activity of Curcuma longa rhizome ethanolic extract (CLRE) on thioacetamide-induced liver cirrhosis in rats.